Soziale Absicherung von Soldaten bei Körperschäden Verfassungsrechtliche Ausgleichsgründe unter besonderer Berücksichtigung von militärischen Verwendungen im Ausland - Gummert, Nils (Universitätsverlag Göttingen, 2023)
If injured or wounded soldiers suffer permanent physical or psychological limitations, the question of social security arises after leaving active service. This problem has become particularly apparent again with the increasing military use of the Bundeswehr in missions abroad. Since then, the legislature has attempted to adapt the traditional pension system to the new circumstances on several occasions. The reorganization of the social compensation law once again provides an opportunity to fundamentally question the legal concept of the military pension system. Against this background, the study analyzes the constitutional framework of the law on military pensions. In particular, it shows that compensation for physical or psychological losses resulting from military service is not a voluntary benefit of the state, but on the one hand already results from the constitutionally anchored commitment of soldiers to their employer, and on the other hand can be based on fundamental legal considerations.